XEB - Zhi Tang; Liangcai Gao; Aixia Jia; Xiaofan Lin (Proceedings of the 9th ACM/IEEE-CS joint conference on Digital libraries, 2009)
Introduction One of the roles of health care providers, and especially nurses, is to routinely provide verbal, written, or even media-based information to patients about catheter care. However, many patients report that they do not receive enough education about catheter care and adverse events while their catheters are in place. Moreover, many report feeling overwhelmed with challenges related to their urinary catheter and resort to trial and error approaches or unreliable, internet-based information. Objectives The aim of this evidence-based implementation project was to improve patient education on indwelling urinary catheter self-management in two hospitals in Iran. Methods This project used the JBI Evidence Implementation Framework. The JBI Framework is grounded in an audit and feedback process with a structured approach to identifying and managing barriers to compliance with recommended clinical practices. Baseline and follow-up audits were used to measure initial compliance with best practices and any improvements following implementation of strategies. A total of 61 patients participated in the audits. Results At baseline, only 3 of the 12 audit criteria reached over 70% compliance, while the remainder were below 50%. Following implementation of a standardized checklist, staff training, and nurse-led follow-up, compliance rates markedly improved, with most criteria exceeding 85%. Conclusions The project highlighted improvements in patient education on urinary catheter care in two urology wards. However, the lack of uniform application of criteria across sites and the absence of direct measurement of clinical outcomes should be considered when interpreting the findings. Spanish abstract https://links.lww.com/IJEBH/A671.